Phytostabilization of arsenic and associated physio-anatomical changes in Acanthus ilicifolius L. (1st April 2022) - Sarath, Nair G.; Shackira, A.M.; El-Serehy, Hamed A.; Hefft, Daniel Ingo; Puthur, Jos T.
Abstract: The carcinogenic attribute of arsenic (As) has turned the world to focus more on the decontamination and declining the present level of As from the environment especially from the soil and water bodies. Phytoremediation has achieved a status of sustainable and eco-friendly approach of decontaminating pollutants, and in the present study, an attempt has been made to reveal the potential of As remediation by a halophyte plant, Acanthus ilicifolius L. Special attention has given to analyse the morphological, physiological and anatomical modulations in A. ilicifolius, developed in response to altering concentrations of Na2 AsO4 .7H2 O (0, 70, 80 and 90 μM). Growth of A. ilicifolius under As treatments were diminished as assessed from the reduction in leaf area, root length, dry matter accumulation, and tissue water status. However, the plants exhibited a comparatively higher tolerance index (44%) even when grown in the higher concentrations of As (90 μM). Arsenic treatment induced reduction in the photochemical activities as revealed by the pigment content, chlorophyll stability index (CSI) and Chlorophyll a fluorescence parameter. Interestingly, the thickness and diameter of the xylem walls in the leaf as well as root tissues of As treated samples increased upon increasing the As concentration. The adaptive strategies exhibited by A. ilicifolius towards varying concentrations of As is the result of coordinated responses of morpho-physiological and anatomical attributes, which make the plant a promising candidate for As remediation, especially in wetlands.